2020
DOI: 10.1155/2020/2412780
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Solar Panel Orientation on the Integration of Solar Energy in Low-Voltage Distribution Grids

Abstract: In Belgium, and many other countries, rooftop solar panels are becoming a ubiquitous form of decentralised energy production. The increasing share of these distributed installations however imposes many challenges on the operators of the low-voltage distribution grid. They must keep the voltage levels and voltage balance on their grids in check and are often regulatory required to provide sufficient reception capacity for new power producing installations. By placing solar panels in different inclinations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 23 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Although this high generation also causes the highest curtailment and grid losses, changing the orientation did not lead to more useful energy. The authors also found, however, that changing the tilt angle had a higher impact on the grid than on the generation and thus suggested to lower tilt angles for more constrained grids (Laveyne et al, 2020).…”
Section: Simulation and Optimization Of Solar Based Energy Systemsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although this high generation also causes the highest curtailment and grid losses, changing the orientation did not lead to more useful energy. The authors also found, however, that changing the tilt angle had a higher impact on the grid than on the generation and thus suggested to lower tilt angles for more constrained grids (Laveyne et al, 2020).…”
Section: Simulation and Optimization Of Solar Based Energy Systemsmentioning
confidence: 97%
“…Not all researchers, however, have agreed with the result that slightly west-oriented panels are the most optimal configuration. A recent study by Laveyne et al (2020) investigated the impact of the orientation of PV modules on the grid, including the effects on grid losses and PV curtailment. Their results identified that the optimal orientation is the one that maximizes the annual generated electricity (south, 35°tilt in Belgium).…”
Section: Simulation and Optimization Of Solar Based Energy Systemsmentioning
confidence: 99%
“…Solar energy production estimates depend on the solar resource and the design of the PV plant to produce power. The output of a PV system is dependent on the amount of solar irradiance received by the active surface of the PV panels (Laveyne et al, 2020). With the reference of Li and Lam (2007), Tiwari and Dubey (2010), we propose a simple formula for calculating annual gross solar PV panels output is based on the PV plant capacity (100 MW) times the total aggregated daily GHI values at the plant location for a year.…”
Section: Modeling and Forecasting Energy Production For Solar Pv Powe...mentioning
confidence: 99%
“…In particular, parameters such as azimuth and tilt angles have been found to play indispensable roles in dispatchability and stability of solar-based energy systems, with poor positioning leading always to an under-performing system. This challenge was the focus of the study presented by Laveyne et al [108], with reference to a solar-based grid-integrated distributed power system for residential applications. Specifically, real irradiation data and parameters of an existing distribution grid were employed to investigate the effects of PV panels' inclinations and azimuth angles on power output and stability of a low-voltage residential distribution grid.…”
Section: Solar Energymentioning
confidence: 99%